Skin and brain age together: The role of hormones in the ageing process - Makrantonaki, Evgenia; Schönknecht, Peter; Hossini, Amir M.; Kaiser, Elmar; Katsouli, Myrto-Maria; Adjaye, James; Schröder, Johannes; Zouboulis, Christos C. (Experimental gerontology, 2010)
The importance of the endocrine environment in the initiation of the ageing process has been elucidated in several in vivo and in vitro studies. Changes in endocrine pathways accompany healthy ageing, these include the growth hormone/insulin-like growth factor-I axis (somatopause) and that of sexual hormones, namely estradiol (menopause), testosterone (andropause), and dehydroepiandrosterone and its sulphate (adrenopause). The clinical significance of these changes is variable and results in morphological and functional alterations of all organ systems including the skin and the central nervous system. Moreover, the pathogenesis of age-associated diseases such as epithelial skin cancer and neurodegenerative diseases has been partly attributed to the lack of hormones. Several studies have been conducted in an attempt to reverse the ageing process and clinical signs by substitution of the serum hormone levels in older individuals, however the benefits of hormone replacement therapy, if any, are still controversial. On the other hand, recent data suggest that skin is a window to the human organism and represents an adequate model for ageing research, also implying the use of skin samples for evaluating the ageing status of the central nervous system.